Perlindungan Terhadap Orang Tanpa Kewarganegaraan (Stateless People) dalam Hukum Internasional (Studi Kasus Etnis Rohingya di Myanmar) - Sigit, Rahmawati Novia; Novianti, Novianti (Faculty of Law, Universitas Jambi, 2020)
This article aims to describe and analyse the regulation of International Law relating to the protection of stateless people through the case of Rohingya in Myanmar. The types of approachment use in this article are statute, case and historical approaches. As a normative study, this article shows that the ethnic protection from discrimination and violence in International Law has been carried out by the United Nations through various international declarations and conventions. Myanmar should ratify Convention Relating to The Stateless Person 1954 and the Convention on the Reduction of Statelessness 1961 as part of its obligations and responsibilities to protect and ensure that Rohingyas have their citizenship.